Successful Emergency Percutaneous Coronary Intervention of Challenging Unprotected Left Main Coronary Artery Disease Patient: How to Prepare and Optimize - Suprayoga, Imam Mi'raj; Rohman, Mohammad Saifur; Martini, Heny; Satrijo, Budi (Heart Science Journal, 2024)
Background: Myocardial infarction (MI) due to unprotected left main coronary artery disease (ULMCAD) is a relatively uncommon presentation. It represents as the anatomical subset of coronary artery disease (CAD) with the highest risk of atherosclerotic obstructive CAD. In the setting of acute MI, the treatment options are limited in this particular condition. Major advances in the field of PCI have made PCI as a viable option for patients with ULMCAD who are equally suited for CABG or PCI.Objective: This study aimed to describe the contemporary evidence PCI for ULMCADCase presentation: A man was admitted to our hospital with crescendo angina accompanied with dyspnea. Electrocardiogram (ECG) showed biphasic t wave on V2-V5 leads. He continued to experience symptoms of ischemia and had increased serial cardiac enzymes. Intra-aortic balloon pump (IABP) support was implemented before performing the PCI. After eight days of hospitalization, he was discharged with stable hemodynamics. Conclusion: PCI has risks and advantages when performed on patients with complex CAD, including ULMCAD. The prognosis for this high-risk patient group can be improved with thorough preparation and effective treatment strategies.